2014
DOI: 10.1037/a0037690
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric structure of the Chinese Multiethnic Adolescent Cultural Identity Questionnaire.

Abstract: In this study, we used the Chinese Multiethnic Adolescent Cultural Identity Questionnaire (CMACIQ) and collected valid data from 1,036 participants to systematically examine the mental model of cultural identity in Chinese multiethnic adolescents. Exploratory factor analysis and structural equation modeling were performed on the data to discover the factor structure and dimensions of cultural identity. The psychometric properties of the scale were rigorously validated in 2,744 new multiethnic participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In the process of integrating different cultural identities, individuals with a harmonious cultural orientation are more likely to be psychologically well adapted and satisfied with their lives (Mok et al, 2007;Yang et al, 2015;Hu et al, 2016). Ethnic minority teenagers have consisten ethnic cultural identity (Hu et al, 2014). Therefore, from the perspectives of culture and collective identity, awe that is embodied in traditional culture can partially explain the ethnic differences in life satisfaction among primary school teachers.…”
Section: The Moderating Role Of National Attributes Between Awe and Life Satisfactionmentioning
confidence: 99%
“…In the process of integrating different cultural identities, individuals with a harmonious cultural orientation are more likely to be psychologically well adapted and satisfied with their lives (Mok et al, 2007;Yang et al, 2015;Hu et al, 2016). Ethnic minority teenagers have consisten ethnic cultural identity (Hu et al, 2014). Therefore, from the perspectives of culture and collective identity, awe that is embodied in traditional culture can partially explain the ethnic differences in life satisfaction among primary school teachers.…”
Section: The Moderating Role Of National Attributes Between Awe and Life Satisfactionmentioning
confidence: 99%
“…As we all know, China is composed of 56 ethnic groups (including 55 minority ethnic groups), with Han Chinese as the majority. And different minority ethnic groups have their unique values and ways of life, 22 but priority is given to Han ethnicity. So paired comparison showed that between community-based care and home-based self-care, Han Chinese participants preferred community-based care, which can satisfy most of their lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…The initial item pools of the CMEVQ and CMEVEBQ were generated following a semi-structured questionnaire, in-depth interviews with ethnic minorities, and existing questionnaires related to ethnic values (Hou, 2008; Tu, 2010; Hu et al, 2014) and ethnic behavior (Phinney, 1992; Phinney and Ong, 2007; Gaines et al, 2016). In addition to the demographic measures, the semi-structured questionnaires and interviews included the following open-ended questions: (1) Concerning minority ethnic consciousness: (a) Under what circumstances can you perceive your minority ethnic identity?…”
Section: Methodsmentioning
confidence: 99%
“…Participants responded to a series of scales online: the CMEVQ and CMEVEBQ scales developed in Study 1; the Inclusion of Ingroup in the Self (IIS; Tropp and Wright, 2001); the Chinese Multiethnic Adolescent Cultural Identity Questionnaire (CMACIQ; Hu et al, 2014); the Ethnic Self-Categorization (ESC; Verkuyten and De Wolf, 2002); the Collective Self-Esteem Scale (CSE); and demographic questions.…”
Section: Methodsmentioning
confidence: 99%